Assessment of Nurses' Practices Concerning Blood Pressure Measurements - Rifaie Y. Hameed; Rami R. Allo (College of Nursing,University of Mosul, 2018)
Background and Aim- Blood Pressure Measurement (BPM) is considered a generic skill required in nursing, by a range of health professionals, for effective health assessment. The study aimed to assess nurses' techniques regarding correct way of measurement of blood pressure. Methods and Materials- A cross-sectional study was conducted on (241) nurses obtained accidently from different wards or units in three teaching hospitals in Mosul City/Iraq during a period "20th of novmber 2017 to 20th of January / 2018". The instruments depended in the study was Global scale of World Health Organization (WHO) that was developed to contain (19) items of two options (Don't do=0 ; Do=1). Observational method was depended by the researchers to collect the data and fulfill the scale while the nurse measured the patient's blood pressure. Results- The study found that practice level of BP measuring was less than acceptable (42.11%). Conclusion and Recommendation- The study concluded that whenever, the patient's complaint is critical, the nurse technique of BP measurement ameliorates. It emphasizes on continuous education of all nurses regarding this nursing procedure to check and validate the health status of the patients in order to reduce potential adverse effect. Key Wards; Nurse, Blood Pressure Measurement.